Antimicrobial activity of Weissella cibaria strains and the contribution of organic acids against food-associated target microorganisms - Camila Gonçalves Teixeira; Cleonice Aparecida Salgado; Tomás Gomes Reis Veloso; Sidney Rodrigues de Jesus Silva; Cecilia de Souza Costa; Solimar Gonçalves Machado; Cinzia Lucia Randazzo; Antônio Fernandes de Carvalho (Brazilian Journal of Microbiology, 2026)
Weissella cibaria , a heterofermentative lactic acid bacterium, is recognized for its antimicrobial activity against a range of pathogenic microorganisms. Therefore, the objective of this study was to evaluate the antimicrobial potential of W. cibaria strains, with an emphasis on their organic acids, against target microorganisms commonly associated with milk and dairy products ( Listeria monocytogenes , Escherichia coli, Staphylococcus aureus , and Salmonella ). To this end, this study evaluated the minimum inhibitory concentration (MIC) of cell-free supernatants (CFS) from three W. cibaria strains (W21, W25, and W42) and their 1:1:1 mixture. Furthermore, the CFS mixture was used in a cheese-simulating matrix to inhibit the target microorganisms. Using HPLC, the organic acids present in the CFS were identified and quantified. Finally, combinations of identified synthetic organic acids were tested for effective inhibition of the target microorganisms. The CFS from strains W21 and W25 and the CFS mixture exhibited better MIC, while a higher concentration of the CFS from W42 was required to inhibit the tested strains. In a cheese-simulating matrix, the CFS mixture significantly reduced the survival rate of the target microorganisms (p < 0.05). By HPLC, the organic acids detected were lactic, acetic, isovaleric, propionic, butyric, valeric, and malic acids. Strain W42 stood out for the absence of isovaleric and valeric acids, while strain W25 stood out for the absence of malic acid. A total of 127 combinations of synthetic organic acids were formulated. L. monocytogenes and Salmonella were predominantly inhibited by combinations of three acids, while E. coli and S. aureus were predominantly inhibited by combinations of 4 or 5 acids and 3 or 5 acids, respectively. The predominance of lactic, acetic, and isovaleric acids was associated with inhibition of the tested microorganisms, while valeric acid was not required for the inhibitory effect of the most effective combinations. These findings support the use of W. cibaria CFS as a potential natural antimicrobial strategy in dairy products and indicate that organic acid combinations may contribute to the inhibition of food-associated microorganisms.